Nonequilibrium drift-diffusion model for organic semiconductor devices - Felekidis, Nikolaos; Melianas, Armantas; Kemerink, Martijn (Physical review, 2016)
DiVA portal is a finding tool for research publications and student theses written at the following 49 universities and research institutions.